Pronomina Gender sebagai Produksi Budaya dalam Unggahan Aktor Transgender di Instagram: Analisis Bourdieusian - Ayu, Dara Mela (Research Community for Critical Society and Environment, 2026)
This study examines the production of gender pronouns as a form of cultural production in Elliot Page’s Instagram coming‑out post published on December 2, 2020, in which he publicly identifies as transgender and adopts the pronouns he/they. Situated within the broader context of digital media and gender discourse, this research aims to understand how language practices related to gender identity are produced, represented, and circulated in contemporary social media spaces. Employing a qualitative approach, the study analyzes both linguistic choices and visual elements present in the Instagram post, alongside selected audience responses in the comment section. Pierre Bourdieu’s theory of cultural production provides the main analytical framework, particularly through the concepts of habits, cultural capital, social capital, and arena. The findings suggest that Page’s position as a well‑known public figure enables the strategic use of pronouns he/they as a symbolic practice supported by significant cultural and social capital. Audience reactions demonstrate a process of symbolic negotiation marked by affirmation, solidarity, and resistance, reflecting broader tensions surrounding gender norms and identity recognition. This study contributes to a deeper understanding of how gender identity is constructed and contested in the digital era and emphasizes social media’s role as an influential arena for cultural production and symbolic power.